PENGARUH ROE, EPS, CR DAN DER TERHADAP HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR PERTAMBANGAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2016 - Anbiya, Resti Al; Saryadi, Saryadi (Jurnal Ilmu Administrasi Bisnis, 2018)
Based on stock price at sectoral index listed in the Indonesia Stock Exchange (BEI), the mining sector is decreasing significantly in stock price for two years since 2014, especially on coal mining subsector. This decrease can be affected by many factors. To know these factors, this research is using fundamental analysis with financial ratio analysis. The type of this research is explanatory research with the population of all coal mining subsektor companies that listed in Indonesia Stock Exchange (BEI) year 2013-2016 specifically 24 companies. However, there is only 16 coal mining subsector companies which qualified. The data used is secondary data from the Company’s Financial Statement published at Indonesia Stock Exhange (BEI) in the form of panel data. The analysis technique used is correlation, determination, simple linear regression analysis, multiple linear regression analysis and significance test by using SPSS 21 version data processing application. This research shows that partially EPS have a positive and significant effect on stock price. While the other variable which is ROE, CR dan DER has no significant effect on stock price. Simultaneously, ROE, EPS, CR and DER has significant effect on stock price. Based on multiple linear regression analysis, EPS has the biggest effect on stock price. Therefore, investors should use EPS factor as a basic of main decision making before investing in coal mining subsector companies.